Pharmacologic Modulation during Cytokine Storm in COVID-19 - Luiza Gabunia; Shrena Khetsuriani; Natia Gamkrelidze; Levan Ratiani; Natalia Filipets; Levan Metreveli; Nodar Sulashvili; Natia Antia (International Journal of Applied Sciences: Current and Future Research Trends, 2021)
The novel Coronavirus -SARS-CoV-2 activates macrophages in order to liberate cytokines into the bloodstream. Inflammatory cytokine secretion increases producing cytokine storm. In this phase significant lymphopenia occurs. Cytokine storm in response to the viral infection can result in sepsis. Ferritin is an important indicator of immune dysregulation, extreme hyperferritinemia, via direct immune-suppressive and proinflammatory effects, contributes to the cytokine storm.There are discussed some clinical evidences that indicate the importance of anti-inflammatory and cytokine-targeted therapies.These approaches are: inhibition of IL-1, IL-6, TNF-? and IFN-?. Alternative treatments for cytokine storm - therapeutic plasma exchange and the mode of action of colchicine, glucocorticoids, and intravenous immunoglobulin - are also discussed. Convalescent plasma, anti-inflammatory treatment, together with anti-viral therapy becomes an essential part of treatment for COVID-19 infection.